Petras Leonas and the Beginnings of Sociology in Lithuania - Genzelis, Bronius (Sociologija. Mintis ir veiksmas, 1999)
The aim of the article is to analyze the historical development of sociology in Lithuania in the beginning of the twentieth century. The author notes that despite the interest in sociological analysis the institutional grounds were lacking. The author argues that the development of sociology as a discipline in Lithuania is closely connected with the work of Petras Leonas. While Mykolas Riomeris might be considered as the first to apply sociological methods for the analysis of social phenomena, it was Petras Leonas who started to lecture sociology at the end of his life.